Meperidine: opioid not indicated for analgesia - Botan,Andresa Graciutti (2015)
BACKGROUND AND OBJECTIVES: Pain evaluation and the choice of the analgesic best providing its control are extremely important for patients’ quality of life. This study aimed at describing the characteristics which make meperidine unfeasible for pain management, at calling the attention to the incidence of its prescriptions and to the need of a multidisciplinary educative action aiming at decreasing its use, in addition to presenting two opioids as options for analgesia. CONTENTS: National or international scientific and governmental publications between the years 1997 and 2013 used in this study report that meperidine is not indicated for pain management, primarily due to its short action time, presence of neurotoxic metabolite (normeperidine) and possibility of rapidly developing tolerance. CONCLUSION: According to analyzed data, meperidine was the most widely used opioid for analgesic or was among the most prescribed analgesics. This fact shows the real need for an educative multidisciplinary action to promote awareness of meperidine risks and to decrease its prescription. According to searched literature, morphine and methadone have longer action time and higher analgesic potency, with metabolites which are less toxic and noxious for patients as compared to meperidine.